Metabolic Risk Factors and Cardiovascular Safety in Ketamine Use for Treatment Resistant Depression - Szarmach J (Dove Medical Press, 2020)
Joanna Szarmach, Wiesław Jerzy Cubała, Adam Włodarczyk, Maria Gałuszko-Węgielnik Department of Psychiatry, Faculty of Medicine, Medical University of Gdańsk, Gdańsk, PolandCorrespondence: Adam WłodarczykDepartment of Psychiatry, Faculty of Medicine, Medical University of Gdansk, 7 Dębinki Street, Building 25, Gdansk 80– 952, PolandEmail aswlodarczyk@gumed.edu.plIntroduction: Ketamine exhibits antidepressant properties in treatment-resistant depression (TRD) with some concern over its cardiovascular safety and tolerability issues. This paper reports on the cardiovascular safety in short-term intravenous ketamine treatment in TRD inpatients with major depressive disorder (MDD) and bipolar disorder (BP).Materials and Methods: The observational study population comprises 35 MDD and 14 BP subjects treated with intravenous ketamine.Results: Blood pressure (RR) and heart rate (HR) values returned to baseline within 1.5-hours post infusion with no sequelae for all study subjects. Six time points were analyzed for each infusion: 0’, 15’, 30’, 45’, 60’ and 90’ for RR and HR. After the infusion significant peaks in systolic (p = 0.004) and diastolic (p = 0.038) RR were seen. In concomitant medication with selective serotonin reuptake inhibitors (SSRIs), higher RR peaks (p = 0.020; p = 0.048) were seen as compared to other subjects. The decrease in HR was greater (p = 0.02) in the absence of concomitant medication with mood stabilizers as compared to subjects receiving mood stabilizing medication accompanied by the observation of a greater decrease in diastolic RR among those taking mood stabilizers (p = 0.009).Limitations: The study may be underpowered due to the small sample size. The observations apply to an inhomogeneous TRD population in a single-site, pilot study, with no blinding and are limited to the acute administration.Conclusion: The study demonstrates good safety and tolerability profile of intravenous ketamine as add-on intervention to current psychotropic medication in TRD, regardless of the MDD or BP type of mood disorders. The abatement of elevated RR and BP scores was observed in time with no sequelae nor harm. Still, cardiovascular risks appear to be more pronounced in subjects with comorbid arterial hypertension and diabetes mellitus.Keywords: ketamine, treatment resistant depression, major depressive disorder, bipolar disorder, cardiovascular, safety, tolerability